Temporary Hubs for the Global Vehicle Supply Chain in Humanitarian Operations - Stauffer, Jon M.; Pedraza‐Martinez, Alfonso J.; Van Wassenhove, Luk N. (Production and Operations Management, 2016)
We model the global vehicle supply chain of an International Humanitarian Organization (IHO) with a dynamic hub location model across monthly periods. We use actual vehicle data from the International Federation of the Red Cross to feed our model and provide insights into IHO secondary support demand. We find that secondary support demand for items such as vehicles is different from primary beneficiary demand for items such as water and food. When considering disaster response and development program demand simultaneously (disaster cycle management), our results illustrate that keeping a lean centralized hub configuration with an option for temporary hubs in mega disaster locations can reduce overall supply chain costs over a long time horizon. We also show that it is possible to structure a supply chain to take operational advantage of earmarked funding. This research lays the groundwork for using optimization models to analyze disaster cycle management.